IMPLEMENTASI PEMBELAJARAN PKN UNTUK MENGUATKAN KARAKTER SISWA SEBAGAI TINDAKAN PREVENTIF BULLYING DI SEKOLAH DASAR - Utsman, Arif (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
The purpose of this study was to determine the implementation of Civics learning to strengthen the character of students as a preventive measure against bullying at SD Negeri 3 Parangharjo. To obtain guidelines for the steps in revealing the problems in the study, a research approach was determined, namely descriptive qualitative. The objects in this study were classroom teachers, and students of SD Negeri 3 Parangharjo, Wonogiri Regency. Because the subject is directly related to the implementation of Civics learning to strengthen the character of students as a preventive measure against bullying. For data collection needs, the types of instruments used are: (1) interviews and (2) observations. The data analysis used is descriptive qualitative data analysis. The implementation of Civics learning to strengthen the character of students as a preventive measure against bullying at SD Negeri 3 Parangharjo is carried out by strengthening indicators of social care character, democratic character, peace-loving character, social solidarity and responsibility character. The results of the research show that Citizenship Education (PKn) has an important role in overcoming cases of bullying among students as proven by the conditions at SDN 3 Parangharjo, namely a more positive classroom atmosphere: Creating a classroom atmosphere that is more inclusive, respectful of each other, and free from intimidation. , Active involvement of students in anti-bullying activities: Increased student participation in activities aimed at preventing bullying, such as forming peer support groups or participating in mentoring programs. Support from all school components: Formation of synergy between teachers, students, parents and the school in an effort to prevent bullying.